Modelling Support Mechanism Impact on Electric Vehicle Registration in Latvia - Gudzuks Gustavs; Cakula Sarma (Economics and Business)
Globalization has led to an increased anthropological impact on the climate, and transport is one of the most greenhouse gas (GHG) intensive sectors that is facilitating it. Transport generated around 14 percent of global GHG emissions in 2010. Transport decarbonization is vital for limiting climate change, and electric vehicle (EV) is one of the solutions. EV prevalence in Latvia after Climate Financial Instrument (CCFI) funding has steadily increased and the average yearly EV growth has remained at 0.09 percent among newly registered light-duty passenger vehicles. The aim of this research is to model the impact of different direct and indirect support mechanisms on EV growth in Latvia taking into account the costs of the given support mechanisms. Accordingly, theoretical literature and research on vehicle decarbonization, EV support mechanisms, and barriers were analyzed. In order to obtain the data related to individual attitude towards EVs and their support policies a survey of different age groups was conducted. Based on the theoretical literature, a model was devised using STELLA software. The model was verified and validated. The results of the model indicate that until 2030 direct subsidies of at least 45 percent will have the largest impact on EV registration, while decreasing VAT by at least 9 percent is the most cost-effective option. The results regarding indirect support mechanisms show that free charging and development of charging infrastructure, as well as improvements to EV related technologies would increase EV registration. However, to ensure sustainable support to EVs it is advisable to combine direct incentives with indirect support mechanisms. Combining different policies lowers incentive costs and increases their efficiency.